The folklore of Discworld : legends, myths, and customs from the Discworld with helpful hints from planet Earth - Pratchett, Terry (Anchor Books, 2014)
The Folklore of Discworld, coauthored by Terry Pratchett and leading British folklorist Jacqueline Simpson, is an invaluable reference for longtime Discworld fans and newcomers alike. An irreverent yet illuminating look at the living myths and folklore that are reflected, celebrated, and affectionately libeled in the uniquely imaginative universe of Discworld. Legends, myths, fairytales, superstitions. Our world is full of the stories we have told ourselves about where we came from and how we got there. It is the same on Discworld, except that beings such as vampires, trolls, golems, witches and, possibly, gods, which on Earth are creatures of the imagination, are real, alive, and in some cases kicking on the Disc. --